KEBIJAKAN MANAJEMEN LABA (Fokus Ekonomi, 2009)
Earnings management is a phenomenon, which has contributed to the development of accounting theory. The term earnings management occurs as a direct consequence of the efforts undertaken by managers or preparers of financial statements in an attempt to affect accounting information, especially earnings, for his/her own and/or company’s benefits. Earnings management can not be interpreted as a negative action since it does not solely concern with earnings manipulation. The Generally Accepted Accounting Principles opens the occation to the enterprise policy to use accrual accounting to write the financial impact of the  entity transaction and events that influence the cash in the accounting period. The characteristic of  accrual accounting is management to determine earnings actual reported in the accounting period. Theoretically, there are many ways or methods available for managers or preparers of financial statements to affect reported earnings, Empirical studies have shown that earnings management is evidenced in many economic contexts. Keywords : earning management, financial statement, accounting information